Tatwīr al-mawād al-ta’līmīyah li mahārati al-qirā’ah ‘alā al-madkhal al-ilmī fi al-madrasah al-Munawwarah al-mutawassitah al-islāmīyah Jombang - Rozaq, Abdur (Journal of Language Intelligence and Culture, 2021)
MTs AL Munawarah is one of the madrasas under the auspices of the Al Munawarah Islamic Boarding School in Jombang Regency. The curriculum used in the teaching and learning process at this madrasa is the K13 curriculum. This curriculum is very helpful for teachers in developing learning materials in terms of material exploration to how to present the exercises used. The researchers here want to help develop the teaching materials used in accordance with the characteristics of the k13 curriculum. From this development, new K13-based teaching materials emerged that could be used by teachers, especially Arabic teachers. This research approach using developmental (R & D) for Borg and Gall theory consists of: (1) preliminary study, (2) planning, (3) hypothetical model development, (4) hypothetical model review, (5) revision, (6 ) limited trial, (7) revision of test results. From the previous statement, the researchers determined the formulation of the problem: (1) How to prepare reading learning teaching materials using a scientific approach at MTS Al Munawarah Diwek - Jombang. and (2) the characteristics of the preparation of teaching materials for learning to read using a scientific approach at MTS Al Munawarah Diwek - Jombang. Based on the assessment of design experts obtained 88.3% very good standard. The expert's assessment of the content of the book obtained a very good standard of 81.53%. The assessment of the student and teacher questionnaires came in at 90%, which is at the level of "very good." This case shows that this book is very good to use in teaching Arabic from the results of assessments and suggestions from experts and also from the responses of teachers and students.